ESTIMATION OF WEIGHT- LENGTH RELATIONSHIP AND CONDITION FACTOR OF TWO DOMINANT FISH SPECIES IN EGBE DAM, SOUTHWESTERN NIGERIA - OLADIMEJI, FOLASADE ADESOLA OLA-; OLADIMEJI, TOFUNMI ELIZABETH; OYEWOLE, OLALEKAN SUNDAY (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Information available on the present growth pattern of two important fish species which are Clarias gariepinus and Parachanna obscura at Egbe dam in Ekiti State of Nigeria is limited. Hence, this study was aimed at updating the existing knowledge on the weight-length relationships and condition factors (K) of these dominant fish in the dam. These fish species were sampled and examined between September 2019 and January 2020. The weight-length relationship had a positive correlation coefficient, r, which varied from 0.37 to 0.84 while the coefficient of determination, r2, varied between 14% and 71.3% for the length and weight of male and female of C. gariepinus and P. obscura respectively. These showed the variation that was related in each sex for the two species. The regression coefficient b revealed a negative allometric growth (b<3) for all the specimens analysed. Condition factor values ranged from 0.38 to 0.59 in C. gariepinus and 0.89 to 0.98 in P. obscura. These data could be valuable for setting up a management system for the improvement of the studied fish species.